Further morphological characterization and structural proteins of infectious bursal disease virus. - Hirai, K (1979)
An outer layer surrounding the capsid of infectious bursal disease virus was evident from electron micrographs of intact virus particles having diameters of 62 to 63 nm. The capsid was found to be composed of large morphological units or capsomeres, measuring about 12 nm in diameter. The architecture of the capsid appears to be that of T = 3 symmetry, with a probable 32 morphological units by rotational enhancement of image detail. Structural proteins of infectious bursal disease virus consist of seven species, two major and five minor polypeptides. These are P1 to P7, with molecular weights of 133 x 10(3), 124 x 10(3), 98 x 10(3), 51 x 10(3), 33 x 10(3), 26 x 10(3), and 23 x 10(3), respectively.